Sistem Pendukung Keputusan Pemilihan Kost di Kota Malang menggunakan Metode Analytical Hierarchy Process dan Weighted Product (AHP-WP) - Thareq Ibrahim; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Boarding House is a place to live for people who come from other regions or cities, especially such as students or workers. In the city of Malang, there are many students who come from outside the city to carry out lectures at their university. Especially for Brawijaya University where every year there are thousands of students who come from outside Malang. However, choosing the right boarding house is difficult because there are many factors that can influence students such as price, distance, facilities, surrounding areas, etc. From these problems, a system is needed that can help students choose the right boarding house. The solution to the problem is to create a decision support system. The purpose of this research is to create a decision support system to help students choose the right boarding house. The method used is the Analytical Hierarchy Process and Weighted Product (AHP-WP) method. The results of testing using the Spearman rank method get the best results on the number of alternatives as many as 31 with a value of 0.8362 which states that the relationship between the ranking results of the system and users is very strong.